Facilitating uptake of Aboriginal Adult Health Checks through community engagement and health promotion - Digiacomo, Michelle; Abbott, P.; Davison, J.; Moore, L.; Davidson, Patricia (Radcliffe Medical Press Ltd., 2010)
Background: Adult Health Checks (AHCs) for Aboriginal and Torres Strait Islander people (MBS Item 710) promote comprehensive physical and psychosocial health assessments. Despite the poor uptake of health assessments in Aboriginal and Torres Strait Islander people, a small number of successful implementation initiatives have been reported. In order to ensure uptake of these screening initiatives, there remains a need to demonstrate the feasibility of models of implementing AHCs. Aims: The aim of this paper is to address the process issues and overarching outcomes of a two-day targeted screening and assessment programme to increase the uptake of AHCs at an Aboriginal Community Controlled Medical Service. Method: Clients of an urban Aboriginal Medical Service (AMS) were invited to undertake an AHC during a two-day screening initiative. On-site general practitioners (GPs), nurses, and Aboriginal Health Workers (AHWs) worked within a team to facilitate screenings at an AMS. Barriers and facilitators to the initiative and strategies for quality improvement were discussed by the team. A review of medical notes was undertaken six months following the screening days to document uptake of recommendations.Results: Forty clients undertook AHCs as part of the initiative. In total, 113 diagnostic tests, interventions, specialist referrals and medication initiatives had been enacted within the following six months as a result of screening day visits. Benefits to individual clients, the community, the AMS and staff were identified. Conclusions: The screening day demonstrated feasibility and acceptability of this approach and provides support for its implementation in other health facilities. Importantly, this service was provided in a culturally sensitive framework and within an interdisciplinary teamwork model. This targeted approach increased uptake of assessment items and provided opportunities for health advice and risk factor modification.